The natural compound periplogenin suppresses the growth of prostate carcinoma cells by directly targeting ATP1A1 - Zhang, Xinquan; Pang, Tinglin; Zhang, Haifeng; Horn, Moritz; Michlits, Georg; Dyczynski, Matheus; Zhang, Liqun (Scientific reports, 2024)
Natural compounds constitute a major resource for the development of medicines for multiple diseases. While many natural compounds show strong biological activity, the mechanisms that confer clinical benefits are often elusive and have been attributed to multiple pathways. Periplogenin (PPG), a natural compound isolated from Cortex periplocae , exhibits strong anti-tumor activities in several human cancer cell lines. However, its molecular mode of action remained unclear. In this study, we leveraged a forward genetic screening approach in DU145 prostate cancer cells to uncover the molecular target of PPG using chemical mutagenesis. Next generation sequencing revealed that a single amino acid substitution at amino acid 804 in ATP1A1 (ATPase Na + /K + Transporting Subunit Alpha 1) confers resistance to the cytotoxic activity of PPG. Mechanistically, ATP1A1 T804 forms a hydrogen bond with PPG which is abolished by the T804A substitution in ATP1A1, resulting in resistance to PPG treatment in vitro. Importantly, in vivo, PPG strongly suppressed tumor development in a DU145 xenograft model whereas DU145 xenograft tumors carrying a ATP1A1-T804A mutation were largely unaffected by the treatment. These findings demonstrate that PPG suppresses the growth of DU145 prostate cancer cells in vitro and in vivo by directly binding to ATP1A1 and highlight the power of our unbiased forward genetic screening approach to uncover direct drug target structures at single amino acid resolution.